The role of alley farming in African livestock production - Reynolds, L.; Jabbar, M.A. (1994)
The incorporation of livestock into alley farming systems, in which food or forage crops are grown between hedges of multipurpose trees that are regularly pruned for mulch and/or forage, has been studied for over 10 years in Africa. Prunings from leguminous trees such as Leucaena and gliricidia can be used for mulch, increasing crop yields, but the trees may also be pruned for fodder, especially during fallow periods. The major benefit from supplementing the diet of free-roaming small ruminants in West Africa with the foliage of leguminous trees is increased surivial, and the forage is best directed at late pregnant and lactating females. In East Africa crossbred dairy cows show a significant response in milk production to supplementation with Leucaena. Economic analyses of livestock production show that continuous alley farming in more profitable than alley farming with fallow, or conventional no-tree farming, even when the cost of clearing trees at the end of their useful life is included. Data presented show: effect of prunnings from Leucaena and Gliricidia as mulch with and without fertilizer on maize grain yield, dry matter intake and lactation performance of Ayrshire/Brown Swiss X Sahiwal cows, characteristics and performance of village goat herds receiving or not receiving Leucaena and Gliricidia browse in southwest Nigeria, and present value gross margins from three alternative farming systems in southwest Nigeria.